Investigating the effect of contextual factors on driving: An experimental study. (July 2022) - Li, Guanlong; Li, Yueqing; Craig, Brian; Liu, Xinyu
Highlights: Frequency of speeding was significantly lower in rain condition compared to clear condition. The frequency of speeding was significantly higher under daylight. Drivers had a significant higher number of correct signs recognition under daylight as compared to night. Task completion time in clear weather was significantly shorter than that in rain and fog weather. Workload in rain weather was significantly higher than that in clear and fog weather. Abstract: Alongside human factors, contextual factors are believed to have an ongoing and complex impact on driving outcomes. However, how and to what extent the components of context influence driving outcomes (e.g. rule violations, crash, stress, fatigue) are far beyond full understanding. The purpose of this study is to explore the effects of weather condition, lighting condition and traffic density on driving outcomes. Thirty-six volunteers were enrolled to participate into a driving simulator-based experiment. Each participant was required to complete twelve trials of simulated driving under different sets of scenarios. Driving outcome was measured by five dependent variables: frequency of speeding, frequency of lane deviations, number of correct sign recognition, completion time and workload. The results showed the frequency of speeding was significantly affected by weather condition, lighting condition and traffic density. Lighting condition had a significant effect on number of correct sign recognition. Weather condition, lighting condition and traffic density had significant effects on task completion time. Weather condition and lighting condition had significant effects on driver's workload. The implications of the results could help traffic safety professionals better understand the risk factors that may lead to human errors during driving. Practically, countermeasures could be inspired and developed to mitigate the adverse impacts brought by driving context to minimum.